Transdiaphragmatic Mucormycosis. (19th June 2019) - Koehler, Philipp; Reimer, Robert; Wahba, Roger; Schömig-Markiefka, Birgid; Cornely, Oliver A
Abstract: Mucormycosis is a life-threatening infection. This is the first report of transdiaphragmatic mucormycosis in a series of 3 patients. We observed this phenomenon in 11% of patients. Clinicians should be aware of this possibly underreported entity, and as a consequence we envision more comprehensive imaging studies in patients with mucormycosis.